Social Capital in Sports Organizations: Examining Voluntary Participation in terms of Certain Variables - Cemal ÖZMAN; Mehmet ÖZTAŞ (ümit doğan üstün, 2023)
The present study aimed to examine voluntary participation in sports organizations in terms of certain variables in the context of social capital. The study was designed using the descriptive survey model, one of the quantitative research approaches. The data were collected with the demographic information form and Ucar's (2016) validated and reliable social capital scale. Individuals participated in Street 10K national sports organization in 2022 constituted the study's population. On the other hand, the study sample consisted of 104 volunteers participated in this sports organization. The participants were chosen according to the convenient sampling method. The data were evaluated using the SPSS 23 Windows package program. Internal consistency coefficients were calculated for the data collection instrument, and mean, standard deviation, kurtosis, and skewness values were examined during data analysis. The independent samples t test and the one-way analysis of variance test were used to test the hypotheses. According to the analysed results, there were significant differences in the "group belonging" factor in favor of participants with volunteer experience in fields other than sports. Besides, significant differences were found in the factors of "corporate trust" and "group belonging" in favor of participants who believed that future career advancement would result from voluntary participation.